Absence of VEGFR‐1/Flt‐1 signaling pathway in mice results in insensitivity to discogenic low back pain in an established disc injury mouse model. Issue 6 (25th December 2019) - Qiu, Sujun; Shi, Changgui; Anbazhagan, Arivarasu Natarajan; Das, Vaskar; Arora, Vipin; Kc, Ranjan; Li, Xin; O‐Sullivan, InSug; van Wijnen, Andre; Chintharlapalli, Sudhakar; Gott‐Velis, Gina; Richard, Ripper; et al.
Abstract: Although degenerative disc disease (DDD) and related low back pain (LBP) are growing public health problems, the underlying disease mechanisms remain unclear. An increase in the vascular endothelial growth factor (VEGF) levels in DDD has been reported. This study aimed to examine the role of VEGF receptors (VEGFRs) in DDD, using a mouse model of DDD. Progressive DDD was induced by anterior stabbing of lumbar intervertebral discs in wild type (WT) and VEGFR‐1 tyrosine‐kinase deficient mice ( vegfr‐1 TK−/ − ). Pain assessments were performed weekly for 12 weeks. Histological and immunohistochemical assessments were made for discs, dorsal root ganglions, and spinal cord. Both vegfr‐1 TK − / − and WT mice presented with similar pathological changes in discs with an increased expression of inflammatory cytokines and matrix‐degrading enzymes. Despite the similar pathological patterns, vegfr‐1 TK − / − mice showed insensitivity to pain compared with WT mice. This insensitivity to discogenic pain was related to lower levels of pain factors in the discs and peripheral sensory neurons and lower spinal glial activation in the vegfr‐1 TK − / − mice than in the WT mice. Exogenous stimulation of bovine disc cells with VEGF increased inflammatory and cartilage degrading enzyme. Silencing vegfr‐1 by small‐interfering‐RNA decreased VEGF‐induced expression of pain markers, while silencing vegfr‐2 decreased VEGF‐induced expression of inflammatory and metabolic markers without changing pain markers. This suggests the involvement of VEGFR‐1 signaling specifically in pain transmission. Collectively, our results indicate that the VEGF signaling is involved in DDD. Particularly, VEGFR‐1 is critical for discogenic LBP transmission independent of the degree of disc pathology. Abstract : Degenerative disc disease (DDD) and associated low back pain (LBP) are growing public health problems; however, the underlying disease mechanisms are unclear. Various investigations implicated an increase in vascular endothelial growth factor (VEGF) levels in DDD, correlated not only with the degree of degeneration but also with the severity of LBP. In this study, we demonstrate that VEGFR‐1/Flt‐1 signaling is critical for discogenic LBP transmission and the absence of the VEGFR‐1/Flt‐1 signaling pathway in mice reduces the discogenic LBP independent of the severity of disc degeneration in an established disc injury mouse model.